IMPACT OF ECONOMIC GROWTH RATES ON REAL INCOMES OF THE POPULATION AND THEIR DISTRIBUTION IN RUSSIA - Tatyana B. Yakimova (Векторы благополучия: экономика и социум, 2022)
The existing wage imbalances, low rates of income growth, and their high differentiation have a negative impact on the socio-economic development of Russia, which determines the relevance of this study. The purpose of this work is to analyze the impact of economic growth rates in Russia on the dynamics of per capita income of the population and inequality in its distribution. Methods. Methods of analysis, synthesis, and comparison were used. The main method of research is the method of statistical analysis based on the requirements of an objective and comprehensive analysis of the income of the population. Results and conclusions. Statistical data for the period from 2000 to 2020 are analyzed, showing the growth in the increasing inequality in the distribution of monetary incomes of the population by the amount of per capita monetary income in the country as a whole for the analyzed period. The relationship between the rates of economic growth and the level of differentiation of the population by income is statistically determined. The reasons for this process in Russia are highlighted. After analyzing the degree of differentiation by a set of indicators, among which the main ones were the fund ratio and the Gini coefficient, it was found that economic growth alone does not solve the problem of economic inequality. During the analyzed period, high rates of economic growth in Russia were accompanied by increased differentiation of the population by income, which has its justification. It was also revealed that the real income of the population grows when the economic growth rate, expressed in real GDP growth, exceeds three percent. At the same time, a more tangible improvement in the financial situation of the population is observed at real GDP growth rates of over five percent.